The gap between Parmenides’ argument on Being and his cosmology in the Aristotelian account (Revista Archai, 2023)
In some of the Aristotelian accounts, Parmenides’ thesis is construed in opposition to the philosophy of nature; on the other hand, he is also depicted, in a different context, as a cosmologist, to whom the Stagirite (and a long tradition afterwards, ending with Simplicius) ascribes a theory of becoming and its principles. In this paper, I exhibit and analyse the relevant passages from Physics I 1-3, Metaphysics I 3 and 5 and On generation and corruption I 3, providing an interpretation that aims to solve the apparent paradox, making sense of the information we can gather from Aristotle’s and Simplicius’ testimonies. Eventually, I propose a construal of the Two Ways of fr. 2 with an emphasis on the predicative reading of einai, which could hint at the Parmenidean approach to cosmology that runs in parallel with the argument on Being.